Literasi Digital: Upaya Meningkatkan Kompetensi Berkomunikasi Frater Pasionis Melalui Media Digital - Pandor, Pius; Wijanarko, Robertus; Nirwana, Aditya; Ton, Sekundus Septo Pigang; Dagur, Oswaldus (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Digital literacy is crucial for enhancing communication skills in the technology era. Through digital literacy, Pasionis "Gen Z" are encouraged to improve their communication abilities by becoming adept in digital media. However, based on the initial situation analysis conducted by the Community Service Team (2023), it shows that Pasionis "Gen Z" still lack awareness of the importance of digital literacy. The issues faced by Pasionis "Gen Z" include a lack of awareness about the importance of digital literacy, weak digital communication skills, minimal facilities supporting digital literacy programs, insufficient knowledge on how to enhance communication intelligence through digital media, and a lack of guidance in digital communication. Solutions to these problems involve conducting outreach and workshops to raise awareness about the importance of digital literacy, providing training on how to communicate through digital media, supplying facilities and infrastructure to support digital literacy programs, enhancing knowledge in developing communication intelligence through digital media, and offering guidance in digital communication training programs. The methods used include socialization, training, technology application, guidance, evaluation, and program sustainability. The community service activities were successfully and smoothly carried out, involving responsive Pasionis "Gen Z". The results of the digital literacy seminar demonstrate an improvement in understanding and skills among Pasionis "Gen Z" in becoming proficient in digital media communication.